Optimizing the Production of Micro, Small, and Medium Enterprises Using the Heijunka Method and Single Minute Exchange of Dies - Nando, Fiky Two; Liwaq, Moch Isabil; Rizki, Muhamad Farhan; Pambudi, Vava Surya; Friski, Auviano Bidana (Indonesian Journal of Engineering and Technological Innovation, 2025)
Micro, Small, and Medium Enterprises (MSMEs) producing bags often face production challenges such as long setup times, unbalanced workloads, and excessive inventory, which reduce efficiency and productivity. This study aims to optimize the production process by applying the Heijunka and Single Minute Exchange of Dies (SMED) methods as part of the Lean Manufacturing approach. The analysis was conducted quantitatively based on actual production data of three types of bags over 27 working days with 13 workers and 8 working hours per day. The results show that the Heijunka method successfully leveled production variation into a daily combination of 30 units of Bag A, 33 units of Bag B, and 14 units of Bag C, resulting in a more stable workflow and reduced overproduction. The application of SMED reduced setup time from 1,560 minutes to 327.6 minutes per month, achieving 79% efficiency improvement, and decreased utilization from 105.36% to 102.6%. These findings indicate that the combination of Heijunka and SMED is effective in improving efficiency, flexibility, and production stability in bag SMEs without requiring significant investment, while enabling the company to meet customer demand on time.